Multi aspect investigation of crude oil concentration detecting via optical fiber sensor coated with ZnO/Ag nano-heterostructure - Samavati, A. (Elsevier B.V., 2021)
Determining the crude oil concentration changes as an essential factor in reservoir engineering, via proposed modified optical fiber sensor, offers a novel approach in oil production optimization. A highly sensitive optical fiber probe is fabricated via partially removing the cladding and coating the sensing part with zinc oxide/silver (ZnO/Ag) heterostructre layer. The ZnO outer layer has three configurations including nanoparticle, horizontally and vertically oriented nanorods. The fabricated optical fiber sensors are subjected to detect the crude oil concentration variations through detection of both wavelengths shift and intensity changes. The effect of ZnO outer layer shape, and the type of light source is used, on sensitivity of the probe is examined. Comprehensive investigation on shape dependent structural and optical properties of ZnO outer layer demonstrates that vertically oriented ZnO has larger surface area, higher average dispersion relation, better crystallinity, larger surface roughness and better adhesion (interaction) with crude oil molecules and these characteristics are responsible for its superior performance compare to other ZnO configurations. For the probe coated with vertically aligned ZnO nanorods when the infrared (IR) light source is used, the intensity and wavelength sensitivity of 0.044 dB/Îcrude oil and 0.112 nm/Î crude oil are obtained respectively. Â© 2020 Elsevier Ltd